Flame-retardant thermoplastic elastomer and preparation method thereof
By adopting a halogen-free and phosphorus-free composite flame retardant system in the thermoplastic elastomer, and using the formation of a physical crosslinking network and porous carbon layer, the shortcomings of the existing flame retardant thermoplastic elastomers in terms of flame retardant properties and mechanical properties are solved, and an efficient and environmentally friendly flame retardant effect is achieved.
Patent Information
- Application Number
- CN202510503749.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-07-01
AI Technical Summary
The existing flame retardant thermoplastic elastomers have shortcomings in flame retardant properties and mechanical properties, especially the addition of flame retardant has adverse effects on the mechanical properties of the material, and the environmental hazards of phosphorus-containing and inorganic flame retardants have not been well solved.
A composite flame retardant system without halogen and phosphorus is adopted, including thermoplastic elastomers, polyphenylene ethers, ethylene-propylene-hexene terpolymers, magnesium hydroxide, silica and composite aluminum salt flame retardant, is used to improve the flame retardant and mechanical properties of the material through the formation of a physical cross-linking network and porous carbon layer.
The synergistic effect of significantly improving flame retardant performance and mechanical properties in high-temperature combustion environments is achieved, reducing costs, and solving the environmental hazards of traditional flame retardants.
Smart Images

Figure CN120230365A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of flame retardant polymer materials, and in particular relates to a flame retardant thermoplastic elastomer and a preparation method thereof. Background Art
[0002] Flame-retardant thermoplastic elastomer is a functional polymer material that has both the flexibility and flame retardancy of thermoplastic elastomer (TPE). It combines the elasticity of rubber with the processing convenience of plastic. It is widely used in electronic appliances, automobiles, construction, wires and cables and other fields. When encountering a fire source, it can effectively slow down or prevent the spread of flames, thereby improving the safety performance of the product to meet increasingly stringent fire safety requirements.
[0003] With the increasingly stringent environmental protection requirements and the continuous improvement of material performance requirements, flame-retardant thermoplastic elastomers are also developing towards halogen-free, high-performance, multifunctional and low-cost. The research focus in this field is to develop new and efficient halogen-free flame retardants, optimize formula design and processing technology to improve flame retardancy and comprehensive performance while reducing costs.
[0004] The technicians have carried out a series of research and development activities. For example, the patent application document with application publication number CN117327384A discloses a highly flame-retardant thermoplastic elastomer, including the following raw materials: thermoplastic polyurethane elastomer, paraffin oil, polyester flame retardant, polyethylene resin, styrene resin, antioxidant. After drying the raw materials in a drying oven at 50-55°C, they are added to a mixing torque rheometer. After mixing, a highly flame-retardant thermoplastic elastomer is obtained, which has a UL94 grade of V-0 and excellent flame retardant properties.
[0005] For another example, the patent application document with application publication number CN117186496A discloses a flame retardant composition for flame retardant thermoplastic elastomer and a preparation method thereof. The raw material formula includes the following raw materials in percentage by mass: 93%-99.5% of a halogen-free flame retardant composition, 0.5%-7% of an aromatic diamine compound; the aromatic diamine compound is 3,3'-dichloro-4,4'-diaminodiphenylmethane. The flame retardant properties of the TPU material can be improved by the combined action of the halogen-free flame retardant composition and the solid aromatic diamine compound.
[0006] The flame retardants used in the above materials have certain advantages in flame retardant properties, but the addition of flame retardants has an adverse effect on the mechanical properties of the elastomer material itself. At the same time, the flame retardant efficiency and environmental hazards of phosphorus-containing and inorganic flame retardants have not been well resolved. Therefore, the development of new halogen-free and phosphorus-free flame retardant systems for thermoplastic elastomer materials is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the above problems, in order to further modify the flame retardancy and mechanical properties of thermoplastic elastomer materials, the present application provides a flame-retardant thermoplastic elastomer and a preparation method thereof.
[0008] The present application first provides a flame-retardant thermoplastic elastomer, which comprises the following raw materials in parts by weight: 60-70 parts of thermoplastic elastomer, 20-30 parts of polyphenylene ether, 15-20 parts of ethylene-propylene-hexene terpolymer, 80-100 parts of magnesium hydroxide, 50-75 parts of silicon dioxide, 20-35 parts of composite aluminum salt flame retardant, 2-3.5 parts of silane coupling agent, and 1.5-2 parts of dimethyl sulfoxide.
[0009] Further, the composite aluminum salt flame retardant is prepared by a method comprising the following steps:
[0010] 1) Take deionized water, aluminum sulfate, fumaric acid, and urea, mix them evenly, and obtain a pre-liquid after microwave heating;
[0011] 2) Add ferric chloride to ammonia water, carry out a hydrothermal reaction, and then add polysaccharide and cyclodextrin derivative to continue the reaction to obtain an intermediate liquid;
[0012] 3) Slowly add the pre-liquid to the intermediate liquid, add L-hydroxyproline while stirring, react at a temperature of 95-110 °C, and filter and dry to obtain the product.
[0013] Further, in the step 1), the mass ratio of deionized water, aluminum sulfate, fumaric acid, and urea is 1:(0.15-0.2):(0.3-0.35):(0.05-0.1);
[0014] and / or, in the step 1), the microwave power is 350-500 W.
[0015] Further, in the step 2), the mass ratio of ferric chloride, polysaccharide, and cyclodextrin derivative is 1:(2-2.5):(0.2-0.3);
[0016] and / or, in the step 2), the mass concentration of ammonia water is 25-30%;
[0017] and / or, in the step 2), the polysaccharide is one or more of carrageenan, xanthan gum, guar gum, and sodium alginate.
[0018] Further, in the step 3), the volume ratio of the pre-liquid to the intermediate liquid is 1:(0.5-0.65);
[0019] and / or, in the step 3), the addition amount of L-hydroxyproline accounts for 5-8 wt% of the mass of the intermediate liquid.
[0020] Further, the cyclodextrin derivative is prepared from β-cyclodextrin and 1,4-butanesultone.
[0021] Furthermore, the thermoplastic elastomer is one or more of TPA, TPO, TPU, SEBS, and TPE.
[0022] Furthermore, the silane coupling agent is one or more of phenyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.
[0023] The present application also provides a method for preparing a flame retardant thermoplastic elastomer, comprising the following steps:
[0024] S1: drying the thermoplastic elastomer and polyphenylene ether for standby use, and then mixing and stirring with ethylene-propylene-hexene terpolymer, magnesium hydroxide, silicon dioxide, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide to obtain a mixture;
[0025] S2: The mixture is kneaded, extruded, pelletized and dried by a twin-screw extruder.
[0026] Furthermore, the mixing process is as follows: the screw length-to-diameter ratio is 48:1, and the screw speed is 280-350 r / min.
[0027] Compared with the prior art, this application has the following beneficial effects:
[0028] 1. The present application adopts thermoplastic elastomer, polyphenylene ether, and ethylene-propylene-hexene terpolymer mixed in appropriate proportions, and forms a physical cross-linked network between the three materials, which plays a very good role in strengthening and toughening, and improves the overall tensile strength and elongation at break of the material. In addition, a halogen-free and phosphorus-free composite flame retardant system is adopted. In a high-temperature combustion environment, magnesium hydroxide is decomposed by heat to generate magnesium oxide and water vapor, taking away part of the heat. At the same time, the water vapor generated promotes the formation of a porous carbon layer. In addition, silicon dioxide plays a role in strengthening the structural strength of the porous carbon layer, inhibiting the melting / dripping of the material, maintaining the stability and integrity of the porous carbon layer, and playing a very good heat insulation and flame retardant effect.
[0029] 2. A composite aluminum salt flame retardant is introduced into the halogen-free and phosphorus-free composite flame retardant system of the present application, and a porous organic aluminum salt and a porous organic iron salt are prepared by a mixed reaction of a pre-liquid and an intermediate liquid. On the one hand, the two can provide a certain amount of microporous and mesoporous structure for the system, which can play a role in heat insulation and adsorption of combustible gases before the porous carbon layer is formed; on the other hand, they can catalytically promote the formation of a porous carbon layer, improve the quality of the carbon layer, and consume the free radicals generated in the combustion process, and cooperate with magnesium hydroxide to produce magnesium oxide to promote the carbonization of small molecular products around them, reduce the degree of gas phase combustion reaction, reduce the degree of heat release and smoke release, and further improve the flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The heat release rate curves of Examples 1-3 of this application and the control group;
[0031] Figure 2 Schematic diagram of the total smoke release curve of Examples 1-3 of this application and the control group. Detailed implementation manners
[0032] Next, the technical solutions in the embodiments of the present application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present application.
[0033] Through a large number of experimental studies, the present application provides a flame-retardant thermoplastic elastomer and a preparation method thereof, which uses a variety of halogen-free and phosphorus-free flame retardants in combination to achieve a very good synergistic flame retardant effect.
[0034] The flame-retardant thermoplastic elastomer of the present application comprises the following raw materials in parts by weight: 60-70 parts of thermoplastic elastomer, 20-30 parts of polyphenylene ether, 15-20 parts of ethylene-propylene-hexene terpolymer, 80-100 parts of magnesium hydroxide, 50-75 parts of silicon dioxide, 20-35 parts of composite aluminum salt flame retardant, 2-3.5 parts of silane coupling agent, and 1.5-2 parts of dimethyl sulfoxide.
[0035] Furthermore, the composite aluminum salt flame retardant is prepared by a method comprising the following steps:
[0036] 1) Take deionized water, aluminum sulfate, fumaric acid, and urea, mix them evenly, and obtain a pre-liquid after microwave heating;
[0037] 2) Add ferric chloride to ammonia water, add polysaccharide and cyclodextrin derivative after hydrothermal reaction, and continue to react to obtain an intermediate liquid;
[0038] 3) Slowly add the pre-liquid to the intermediate liquid, add L-hydroxyproline while stirring, react at a temperature of 95-110 °C, and filter and dry to obtain.
[0039] Furthermore, in step 1), the mass ratio of deionized water, aluminum sulfate, fumaric acid, and urea is 1:(0.15-0.2):(0.3-0.35):(0.05-0.1);
[0040] And / or, in step 1), the microwave power is 350-500 W.
[0041] In some specific embodiments, in the step 1), the mass ratio of deionized water, aluminum sulfate, fumaric acid, and urea can be 1:0.15:0.3:0.05, 1:0.18:0.3:0.05, 1:0.2:0.3:0.05, 1:0.15:0.32:0.05, 1:0.15:0.35:0.05, 1:0.15:0.3:0.07, 1:0.15:0.3:0.085, 1:0.15:0.3:0.1, 1:0.17:0.33:0.05, 1:0.2:0.35:0.05, 1:0.15:0.32:0.085, 1:0.15:0.35:0.1, 1:0.18:0.3:0.08, 1:0.2:0.3:0.1, 1:0.17:0.32:0.07, 1:0.18:0.34:0.09, 1:0.2:0.35:0.1. Usually, in the step 1), when the mass ratio of deionized water, aluminum sulfate, fumaric acid, and urea is 1:0.2:0.3:0.08, better experimental results can be obtained.
[0042] In some specific embodiments, in the step 1), the microwave power can be 350W, 400W, 450W, 500W. Usually, in the step 1), when the microwave power is 500W, better experimental results can be obtained.
[0043] Further, in the step 2), the mass ratio of ferric chloride, polysaccharide, and cyclodextrin derivative is 1:(2 - 2.5):(0.2 - 0.3);
[0044] and / or, in the step 2), the mass concentration of ammonia water is 25 - 30%;
[0045] and / or, in the step 2), the polysaccharide is one or more of carrageenan, xanthan gum, guar gum, and sodium alginate.
[0046] In some specific embodiments, in the step 2), the mass ratio of ferric chloride, polysaccharide, and cyclodextrin derivative can be 1:2:0.2, 1:2.1:0.2, 1:2.2:0.2, 1:2.3:0.2, 1:2.4:0.2, 1:2.5:0.2, 1:2:0.22, 1:2:0.24, 1:2:0.26, 1:2:0.28, 1:2:0.3, 1:2.1:0.22, 1:2.2:0.23, 1:2.3:0.25, 1:2.4:0.28, 1:2.5:0.3, 1:25:0.22, 1:2.5:0.25, 1:2.5:0.28, 1:2.5:0.29. Usually, in the step 2), when the mass ratio of ferric chloride, polysaccharide, and cyclodextrin derivative is 1:2.5:0.2, better experimental results can be obtained.
[0047] In some specific embodiments, generally, when the polysaccharide is carrageenan, the experimental effect is better.
[0048] Further, in step 3), the volume ratio of the pre-liquid to the intermediate liquid is 1:(0.5 - 0.65);
[0049] and / or, in step 3), the addition amount of L-hydroxyproline accounts for 5 - 8 wt% of the mass of the intermediate liquid.
[0050] In some specific embodiments, in step 3), the volume ratio of the pre-liquid to the intermediate liquid can be 1:0.5, 1:0.52, 1:0.53, 1:0.55, 1:0.56, 1:0.57, 1:0.58, 1:0.59, 1:0.6, 1:0.62, 1:0.63, 1:0.64, 1:0.65. Generally, in step 3), when the volume ratio of the pre-liquid to the intermediate liquid is 1:0.55, better experimental results can be obtained.
[0051] In some specific embodiments, in step 3), the addition amount of L-hydroxyproline can account for 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt% of the mass of the intermediate liquid. Generally, in step 3), when the addition amount of L-hydroxyproline accounts for 6 wt% of the mass of the intermediate liquid, the experimental effect is better.
[0052] Further, the cyclodextrin derivative is prepared from β-cyclodextrin and 1,4-butanesultone.
[0053] Further, the thermoplastic elastomer is one or more of TPA, TPO, TPU, SEBS, and TPE.
[0054] Further, the silane coupling agent is one or more of phenyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.
[0055] Generally, when the thermoplastic elastomer is SEBS, the experimental effect is better.
[0056] Generally, when the silane coupling agent is γ-mercaptopropyltrimethoxysilane, the experimental effect is better.
[0057] This application also provides a preparation method of a flame-retardant thermoplastic elastomer, including the following steps:
[0058] S1: Dry the thermoplastic elastomer and polyphenylene ether for later use, and then mix and stir them with ethylene-propylene-hexene terpolymer, magnesium hydroxide, silica, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide to obtain a mixture;
[0059] S2: Knead, extrude, and pelletize the mixture through a twin-screw extruder, and obtain the product after drying.
[0060] Furthermore, the kneading process is as follows: the ratio of the screw length to the diameter is 48:1, and the screw speed is 280 - 350 r / min.
[0061] Example 1
[0062] The flame-retardant thermoplastic elastomer of this example comprises the following raw materials in parts by weight: 70 kg of thermoplastic elastomer, 20 kg of polyphenylene ether, 20 kg of ethylene-propylene-hexene terpolymer, 80 kg of magnesium hydroxide, 75 kg of silica, 20 kg of composite aluminum salt flame retardant, 2 kg of silane coupling agent, and 1.5 kg of dimethyl sulfoxide.
[0063] Among them, the thermoplastic elastomer is SEBS, with the model 6153. The model of the polyphenylene ether is 340Z. The composite aluminum salt flame retardant is composed of aluminum hydroxide and aluminum sulfate in a mass ratio of 1:0.2. The silane coupling agent is γ-mercaptopropyltrimethoxysilane.
[0064] The preparation method of the flame-retardant thermoplastic elastomer of this example comprises the following steps:
[0065] S1: Dry the thermoplastic elastomer and polyphenylene ether in a drying oven for later use, and then feed them together with ethylene-propylene-hexene terpolymer, magnesium hydroxide, silica, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide into a high-speed mixer to mix and stir to obtain a mixture;
[0066] S2: Knead, extrude, and pelletize the mixture through a twin-screw extruder, and obtain the product after drying. The ratio of the screw length to the diameter is 48:1, the main screw speed is 300 r / min, and the temperatures of each heating section are 190°C, 200°C, 205°C, 210°C, 210°C, 215°C, 215°C, 220°C, 220°C, 225°C.
[0067] Example 2
[0068] The flame-retardant thermoplastic elastomer of this example comprises the following raw materials in parts by weight: 60 kg of thermoplastic elastomer, 30 kg of polyphenylene ether, 15 kg of ethylene-propylene-hexene terpolymer, 100 kg of magnesium hydroxide, 50 kg of silica, 35 kg of composite aluminum salt flame retardant, 3.5 kg of silane coupling agent, and 2 kg of dimethyl sulfoxide.
[0069] Among them, the thermoplastic elastomer is SEBS, and the model is 6153. The model of polyphenylene ether is 340Z. The silane coupling agent is γ-mercaptopropyltrimethoxysilane.
[0070] The composite aluminum salt flame retardant of this example is prepared by a method including the following steps:
[0071] 1) Take deionized water, aluminum sulfate, fumaric acid, and urea in a mass ratio of 1:0.2:0.3:0.08, mix them evenly, and obtain a pre-liquid after microwave heating at 500W for 3h;
[0072] 2) Add 50 g of ferric chloride to 1.5 L of ammonia water with a mass concentration of 28%, add carrageenan and carboxymethyl β-cyclodextrin after hydrothermal reaction and continue to react to obtain an intermediate liquid, and control the mass ratio of ferric chloride, carrageenan, and carboxymethyl β-cyclodextrin to be 1:2.5:0.2;
[0073] 3) Slowly add the pre-liquid to the intermediate liquid, control the volume ratio of the pre-liquid to the intermediate liquid to be 1:0.5, add L-hydroxyproline accounting for 6 wt% of the mass of the intermediate liquid while stirring, and react at 100 °C for 5 h, then filter and dry to obtain.
[0074] The preparation method of the flame-retardant thermoplastic elastomer of this example includes the following steps:
[0075] S1: Dry the thermoplastic elastomer and polyphenylene ether in a drying oven for standby, and then feed ethylene-propylene-hexene terpolymer, magnesium hydroxide, silicon dioxide, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide into a high-speed mixer and mix and stir to obtain a mixture;
[0076] S2: Knead, extrude, and pelletize the mixture through a twin-screw extruder, and obtain it after drying. The length-diameter ratio of the screw is 48:1, the rotational speed of the screw main engine is 300 r / min, and the temperature of each heating section area is 190 °C, 200 °C, 205 °C, 210 °C, 210 °C, 215 °C, 215 °C, 220 °C, 220 °C, 225 °C.
[0077] Example 3
[0078] The flame-retardant thermoplastic elastomer of this example includes the following raw materials in parts by weight: 60 kg of thermoplastic elastomer, 25 kg of polyphenylene ether, 15 kg of ethylene-propylene-hexene terpolymer, 100 kg of magnesium hydroxide, 50 kg of silicon dioxide, 30 kg of composite aluminum salt flame retardant, 3 kg of silane coupling agent, and 2 kg of dimethyl sulfoxide.
[0079] Among them, the thermoplastic elastomer is SEBS, and the model is 6153. The model of polyphenylene ether is 340Z. The silane coupling agent is γ-mercaptopropyltrimethoxysilane.
[0080] The composite aluminum salt flame retardant of this embodiment is prepared by a method including the following steps:
[0081] 1) Take deionized water, aluminum sulfate, fumaric acid, and urea in a mass ratio of 1:0.2:0.3:0.08, mix them evenly, and obtain a pre-liquid after microwave heating at 500W for 3h;
[0082] 2) Add 50g of ferric chloride to 1.5L of ammonia water with a mass concentration of 28%, add carrageenan and cyclodextrin derivative after hydrothermal reaction and continue to react to obtain an intermediate liquid, and control the mass ratio of ferric chloride, carrageenan, and cyclodextrin derivative to be 1:2.5:0.2;
[0083] 3) Slowly add the pre-liquid to the intermediate liquid, control the volume ratio of the pre-liquid to the intermediate liquid to be 1:0.5, add 6wt% of L-hydroxyproline based on the mass of the intermediate liquid while stirring, react at 100°C for 5h, filter and dry to obtain.
[0084] The cyclodextrin derivative of this embodiment is prepared by the following steps: First, β-cyclodextrin reacts with 1,4-butanesultone to obtain sulfobutyl-β-cyclodextrin, then sulfobutyl-β-cyclodextrin and citric acid are dissolved in deionized water according to a molar ratio of 2:1, mixed evenly and reacted at 100°C for 3h, spin-dried, washed, and dried to obtain.
[0085] The preparation method of the flame-retardant thermoplastic elastomer of this embodiment includes the following steps:
[0086] S1: Dry the thermoplastic elastomer and polyphenylene ether in a drying oven for standby, and then feed them together with ethylene-propylene-hexene terpolymer, magnesium hydroxide, silica, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide into a high-speed mixer for mixing and stirring to obtain a mixture;
[0087] S2: Knead, extrude, and pelletize the mixture through a twin-screw extruder, and dry it to obtain. The length-diameter ratio of the screw is 48:1, the rotational speed of the screw main machine is 300r / min, and the temperature of each heating section area is 190°C, 200°C, 205°C, 210°C, 210°C, 215°C, 215°C, 220°C, 220°C, 225°C.
[0088] Control group
[0089] The flame-retardant thermoplastic elastomer of this control group includes the following raw materials in parts by weight: 70kg of thermoplastic elastomer, 20kg of polyphenylene ether, 20kg of ethylene-propylene-hexene terpolymer, 80kg of magnesium hydroxide, 75kg of silica, 20kg of aluminum hydroxide, 2kg of silane coupling agent, and 1.5kg of dimethyl sulfoxide.
[0090] Among them, the thermoplastic elastomer is SEBS, with the model number 6153. The model number of the polyphenylene ether is 340Z. The silane coupling agent is γ-mercaptopropyltrimethoxysilane.
[0091] The preparation method of the flame-retardant thermoplastic elastomer of this control group includes the following steps:
[0092] S1: Dry the thermoplastic elastomer and the polyphenylene ether in a drying oven for later use, and then feed ethylene-propylene-hexene terpolymer, magnesium hydroxide, silicon dioxide, aluminum hydroxide, silane coupling agent, and dimethyl sulfoxide into a high-speed mixer for mixing and stirring to obtain a mixture;
[0093] S2: Knead, extrude, and pelletize the mixture through a twin-screw extruder, and obtain the product after drying. The length-diameter ratio of the screw is 48:1, the rotational speed of the main screw of the extruder is 300 r / min, and the temperatures of each heating section are 190 °C, 200 °C, 205 °C, 210 °C, 210 °C, 215 °C, 215 °C, 220 °C, 220 °C, and 225 °C.
[0094] Performance testing
[0095] 1. Take the flame-retardant thermoplastic elastomers of Examples 1-3 and the control group, dry them at 80 °C for 3 h, then hot-press and form them through a flat vulcanizer. The hot-press temperature is 190 °C, the pressure is 10 MPa, and the hot-press time is 10 min. After cooling to room temperature, test specimens are obtained. According to GB / T 528-2009, test the tensile strength and elongation at break of the blend material. Set the tensile rate to 200 mm / min, and test five times for each group. The test results are shown in Table 1.
[0096] 2. Take the above specimens, cut them into dimensions of 125 mm × 12.5 mm × 3 mm. Refer to UL-94 "Flammability Test for Plastic Parts of Equipment and Electrical Appliances", and under the specified combustion conditions, comprehensively determine the flame-retardant grade of the material according to the continuous combustion time, self-extinguishing, dripping and other states of the sample. The test results are shown in Table 1. It can be seen that the flame-retardant and mechanical properties of the flame-retardant thermoplastic elastomer of this application are relatively good.
[0097] Table 1 Test data of the mechanical properties and flame-retardant properties of the flame-retardant thermoplastic elastomers of Examples 1-3 and the control group
[0098]
[0099] 3. Take the above specimens, cut them into dimensions of 100 mm × 100 mm × 3 mm. Refer to ISO 5660-1 "Fire Tests - Heat Release, Smoke Production and Mass Loss Rate". During the test, wrap a layer of aluminum foil around the specimen and place it in a combustion box for combustion testing. The test radiation intensity is 50 kW / m 2, a series of combustion-related parameters such as the heat release rate, total heat release, smoke release rate, total smoke release, and mass loss during the material combustion process are obtained, and the test results are as Figure 1 and Figure 2 shown. It can be seen that the composite aluminum salt flame retardant system of the present application can achieve a relatively good flame retardant effect, can promote the formation of a carbon layer, and can achieve a relatively good flame retardant effect in the early stage of combustion. The heat release rate and the amount of smoke released are very low. In the middle and late stages of combustion, it can also consume free radicals, catalytically promote the continuous growth of the carbon layer, and has excellent heat insulation and flame retardant performance.
[0100] Although the present application has been described in detail with reference to the foregoing embodiments, for those skilled in the art, they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present invention.
Claims
1. A flame retardant thermoplastic elastomer, characterized in that: The invention comprises the following raw materials in parts by weight: 60-70 parts of thermoplastic elastomer, 20-30 parts of polyphenylene ether, 15-20 parts of ethylene-propylene-hexene terpolymer, 80-100 parts of magnesium hydroxide, 50-75 parts of silicon dioxide, 20-35 parts of composite aluminum salt flame retardant, 2-3.5 parts of silane coupling agent and 1.5-2 parts of dimethyl sulfoxide.
2. The flame retardant thermoplastic elastomer according to claim 1, characterized in that: The composite aluminum salt flame retardant is prepared by a method comprising the following steps: 1) deionized water, aluminum sulfate, fumaric acid and urea are mixed evenly and heated by microwave to obtain a pre-fluid; 2) adding ferric chloride to ammonia water, adding polysaccharide and cyclodextrin derivative after hydrothermal reaction and continuing the reaction to obtain an intermediate solution; 3) Slowly add the pre-liquid into the intermediate solution, add L-hydroxyproline while stirring, react at 95-110°C, filter and dry to obtain.
3. The flame retardant thermoplastic elastomer according to claim 2, characterized in that: In the step 1), the mass ratio of deionized water, aluminum sulfate, fumaric acid and urea is 1:(0.15-0.2):(0.3-0.35):(0.05-0.1); And / or, in step 1), the microwave power is 350-500W.
4. The flame retardant thermoplastic elastomer according to claim 2, characterized in that: In the step 2), the mass ratio of ferric chloride, polysaccharide and cyclodextrin derivative is 1:(2-2.5):(0.2-0.3); And / or, in step 2), the mass concentration of aqueous ammonia is 25-30%; And / or, in step 2), the polysaccharide is one or more of carrageenan, xanthan gum, guar gum, and sodium alginate.
5. The flame retardant thermoplastic elastomer according to claim 2, characterized in that: In the step 3), the volume ratio of the pre-liquid to the intermediate liquid is 1:(0.5-0.65); And / or, in the step 3), the amount of L-hydroxyproline added is 5-8 wt % of the mass of the intermediate solution.
6. The flame retardant thermoplastic elastomer according to claim 4, characterized in that: The cyclodextrin derivative is prepared from beta-cyclodextrin and 1,4-butanesultone.
7. The flame retardant thermoplastic elastomer according to claim 1, characterized in that: The thermoplastic elastomer is one or more of TPA, TPO, TPU, SEBS and TPE.
8. The flame retardant thermoplastic elastomer according to claim 1, characterized in that: The silane coupling agent is one or more of phenyltrimethoxysilane, vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane.
9. A method for preparing a flame retardant thermoplastic elastomer according to claim 1, characterized in that: The steps include: S1: drying the thermoplastic elastomer and polyphenylene ether for standby use, and then mixing and stirring with ethylene-propylene-hexene terpolymer, magnesium hydroxide, silicon dioxide, composite aluminum salt flame retardant, silane coupling agent, and dimethyl sulfoxide to obtain a mixture; S2: The mixture is kneaded, extruded, pelletized and dried by a twin-screw extruder.
10. The method for preparing a flame retardant thermoplastic elastomer according to claim 9, characterized in that: The mixing process is as follows: the screw length-diameter ratio is 48:1, and the screw speed is 280-350 r / min.
Citation Information
Patent Citations
Flame-retardant composition for flame-retardant thermoplastic elastomer and preparation method of flame-retardant composition
CN117186496A
High-flame-retardant thermoplastic elastomer
CN117327384A